Relationship between Reward and Emotional Intelligence of Academic Staff at Malaysian Public Universities (Journal of Educational, Health and Community Psychology, 2015)
AbstractOne of the great positive behavioral factors among staff at university is emotional intelligence. In reality, emotional intelligence is cause of different reaction at workplace that was appeared by staff and also controlled most of moods in various situations. Moreover, knowing factors that impact on emotional intelligence is very vital and lead to different positive and negative behavior among staff. Reward is one of these external effective factors that influence on emotional intelligence. Present study considered to these two factors and also investigates their association together. The sample of this study made up of 440 academic staff that work in public research universities in Malaysia. The participants completed the emotional intelligence scale. The results indicated that there are significant associations between reward with emotional intelligence items (perception and managing own emotion) that analyzed by t-test. Key word: reward, emotional intelligence, staff, universityOne of the great positive behavioral factors among staff at university is emotional intelligence. In reality, emotional intelligence is cause of different reaction at workplace that was appeared by staff and also controlled most of moods in various situations. Moreover, knowing factors that impact on emotional intelligence is very vital and lead to different positive and negative behavior among staff. Reward is one of these external effective factors that influence on emotional intelligence. Present study considered to these two factors and also investigates their association together. The sample of this study made up of 440 academic staff that work in public research universities in Malaysia. The participants completed the emotional intelligence scale. The results indicated that there are significant associations between reward with emotional intelligence items (perception and managing own emotion) that analyzed by t-test.Key word: reward, emotional intelligence, staff, university